Il puzzle dei ceti medi - Bellini, Andrea (Strumenti per la didattica e la ricerca, 2014)
The issue of the middle class has seen a recovery of interest in public opinion in the last decade, especially in light of the problems connected with the transition to flexible capitalism and the advent of the economic crisis. In the scientific debate, it has been present since the dawn of modern sociology as a phenomenon difficult to frame from the theoretical point of view and even more difficult to empirically investigate. Starting from these premises, the volume offers a critical reinterpretation of classic and contemporary authors and contributions, focusing its analysis on the role played by the middle classes themselves in the process of change, trying to identify and highlight the inter-connections between the size of structure, identity and action.